Sñiṅ thig ya bźi : a collection of important initiations and instructions on Rdzogs-chen practice - Kloṅ-chen-pa Dri-med-ʼod-zer, 1308-1363 (Sherab Gyaltsen Lama, 1975)
Profound instructions on the Dzogehen system of practice of the Nyingmapa tradition.